ANALYSIS OF SPECIFIC AND NON SPECIFIC PARAMETERS OF GOROHO BANANAS (Musa acuminata L.) - Wiwit Zuriati Uno; Rionaldo Arginggang; Lya Yulyani Sulasdi; Makhfudia A. Masulili; Sri Safitri Nasib; Hudan Wijaya (JIMR : Journal Of International Multidisciplinary Research, 2025)
Goroho banana (Musa acuminata subsp. goroho) is a local Indonesian plant with potential as a traditional medicine due to its secondary metabolite content. This study aimed to standardize goroho banana extract through testing specific and nonspecific parameters to ensure the quality, safety, and quality of the extract. The method used was maceration extraction with 96% ethanol. Specific parameters tested included organoleptic testing, water-soluble extract content, ethanol- soluble extract content, and phytochemical screening. Nonspecific parameters included water content and microbial contamination testing. The results showed that goroho banana extract was thick, light yellow, and had a distinctive banana odor. The water-soluble extract and ethanol content were each 16.6%, meeting quality requirements. Phytochemical screening revealed the presence of flavonoids and saponins, while alkaloids yielded negative results in the Mayer test. Nonspecific testing indicated that the water content and microbial contamination were within safe limits according to standards. Based on these results, goroho banana extract meets the quality criteria for herbal extracts and has the potential to be developed as a raw material for traditional medicine